Applied linear statistical models : regression, analysis of variance, and experimental designs - Neter, John.; Wasserman, William (Homewood, Ill. : R. D. Irwin, 1974)
This extensive book on linear statistical models presents a leisurely treatment of a limited range of topics at an elementary level. The treatment is methodological with little formal proof, or demonstration, of the properties of the methods which are described and illustrated. After a brief introductory chapter on "Some basic results in probability and statistics" the book consists of 23 further chapters divided into five Parts entitled: I. Basic Regression Analysis. II. General Regression and Correlation Analysis. III. Basic Analysis of Variance. IV. Multifactor Analysis of Variance. V. Experimental Designs.
Includes bibliographical references and index.
rpm 26/07/2018
Loans
Keywords: Regression analysis; Analysis of variance; Experimental design; Linear models (Statistics).